Removal of Mo/Si multilayer coatings on fused silica substrates by wet chemical etching. (23rd April 2021) - Toyoda, Mitsunori; Yokoyama, Ryo; Waki, Shuntaro; Kakudate, Toshiyuki; Chen, Jun
Abstract: This work examined a novel etching procedure for the complete removal of Mo/Si multilayer coatings, as a means of reusing valuable mirror substrates employed in extreme ultraviolet imaging. A multilayer coating deposited on a fused silica substrate was etched with an alkaline solution containing potassium ferricyanide and sodium hydroxide, and the entire coating was removed within 60 min. The root mean square roughness and power spectrum density characteristics were subsequently assessed and the resulting values were equivalent to those before the deposition of the coating. These results demonstrate that such coatings can be removed while maintaining the original surface figure.